Challenges and opportunities for green transitions adoption in Kenya's textile manufacturing industry - Awino, Dinah (Frontiers in Sustainability, 2025)
IntroductionIn the face of accelerating climate change as a result of fossils, the textile industry has been considered as a significant industrial contributor to global carbon emissions. In Kenya, this sector is responsible for approximately 56% of total industrial pollution, highlighting the urgent need for a transition to sustainable practices. This study, conducted between September 2023 and August 2024, investigates the opportunities and challenges presented in a green transition and practical efforts toward green transition in selected Kenyan textile mills, specifically at the Thika Cloth Mill and Rivatex East Africa company.MethodsUtilizing qualitative data analyzed thematically, the research explored demographic influences on sustainability efforts, revealing critical insights into the barriers and potential pathways for green growth in the industry.ResultsKey findings include significant waste generation in spinning and processing departments, high water dependency, reliance on non-renewable energy sources like coal and firewood, and limited awareness of sustainability practices among industry players. Additionally, the sector faces difficulties in sourcing natural fibers due to low domestic cotton production and climate change impacts. However, initiatives such as Rivatex's establishment of a cotton farm, Thika Cloth Mills' use of coffee husks for biomass energy, and exploration of green dyes from natural sources indicate potential pathways toward sustainability. The study concluded that challenges such as inefficient waste management, heavy reliance on non-renewable energy sources, insufficient domestic cotton production, and limited awareness of environmental standards collectively hinder progress toward a greener sector.DiscussionsThe findings of the present study highlight the multifaceted challenges impeding Kenya's textile industry from fully embracing sustainable practices. Issues such as inefficient waste management, heavy reliance on non-renewable energy sources, insufficient domestic cotton production, and limited awareness of environmental standards collectively hinder progress toward a greener sector. While initiatives like Rivatex's Bt cotton farming and Thika Cloth Mills' use of coffee husks for energy demonstrate steps toward sustainability, these efforts are sporadic and lack comprehensive industry-wide adoption. The absence of stringent environmental regulations and incentives further exacerbates the situation, allowing unsustainable practices to persist.